Diversität in Bibliotheken : Theorien, Strategien und Praxisbeispiele - Hauck, Julia; Linneberg, Sylvia (2021)
Trying to do justice to society’s diversity is a challenge for public libraries. This volume provides an overview of the development of strategic and anti-discrimination organizations and of the work being done in the fields of events and inventory to disseminate information in a way that is sensitive to diversity. It also presents a range of practical examples form the program "360° – Fund for Cultures in the New Urban Society."...